Österreichische Historiker Lebensläufe und Karrieren 1900-1945 - Hruza, Karel (b37bfef0-76f3-443a-82c6-f6a288576e8d, 2012)
The anthology contains 15 elaborate historical scientific portraits of Austrian historians written by 16 historians from Austria, Germany and the Czech Republic. It conceptually follows the first volume distributed in 2008 which contained 18 portraits most positively reviewed by 15 experts until today. The presented historians had been born in the Habsburg monarchy owning or receiving the Austrian nationality after 1918 and went through their decisive mode of activity between 1900 and 1945. There are two historians of art and one orientalist amongst them. In science or other fields they left traces so that the analysis of their biographies brought new scientific historical results. The chosen period of time enters the work of three generations of historians subdivided into the "generation of the youth of war", the "generation of the front lines" and the "precedent generation". At the same time corresponding with an also internationally observed period of the Austrian historical research verified by the following names of the portrayed historians such as Michael Tangl, Max Dvořák, Hugo Dantsch, Heinrich von Srbik oder Karl Lechner. The portrayed historians had been taken despite of their innovative or controversial historical field of work. The portraits cover the most important biographical data even exceeding it since the authors analyzed material from the archives in order to show socio biographical facts. The research work at the archives supports the request of memberships in scientific and political parties and activities in scholarship and research. In addition to that political views and activities and structures of scientific networking were able to be verified. That also shows that in certain student circles and networks above all by the University of Vienna and especially at the Institut für Österreichische Geschichtsforschung, a special Austrian (and also international) scientific component, existed. A central point is the scientific historical implementation of the oeuvre of the portrayed historians. It shows how the works are influenced by the authors impetus received from different sides and how they again effected other historians. The characteristic of time of the writings, their positions and dependence of the present at that time had been brought out clearly. The change of perspective or paradigm due to "external" influences such as the defeat of the war in 1918 or the "annexation" in 1938 is apparent looking at several portrayed historians as well as the sense of resistance by the others. To take up differently the political moment of the portrayed historians in their life and work had been a committed debate above all since the majority of the portrayed historians had taken their political views seriously. All in all the published edition offers a further critical, biographical oriented scientific historical (part of the) profile of the Austrian science of history from 1900-1945.